Material Affinities: ‘Doing’ Family through the Practices of Passing On - Holmes, Helen (Sociology, 2019)
This article explores how mundane objects are passed on through kinship networks and how these practices become part of the ‘doing’ of family and kinship. Using Mason’s concept of affinities, I illuminate four strands of material affinities, each of which illustrates how passed on objects can reproduce, imagine and memorialise kin connections both biological and social, and in and through time. Crucially, I argue that it is everyday objects in use which reveal how materiality and kinship are woven together. By starting from the object rather than the subject material affinities are brought to life, illustrating how materials are inscribed with kinship both physically and imaginatively, but in turn inscribe kinship practices, operating as central characters in family narratives. The article stems from research exploring everyday contemporary thrift and involved one-to-one interviews and a Mass Observation Directive on the subject of ‘Being thrifty’.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDM4MDM4NTE4Nzc3Njk2